2023
DOI: 10.3390/brainsci13050750
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Consciousness and Righting Reflex Following Traumatic Brain Injury: Predictors of Post-Injury Symptom Development (A Narrative Review)

Abstract: Identifying predictors for individuals vulnerable to the adverse effects of traumatic brain injury (TBI) remains an ongoing research pursuit. This is especially important for patients with mild TBI (mTBI), whose condition is often overlooked. TBI severity in humans is determined by several criteria, including the duration of loss of consciousness (LOC): LOC < 30 min for mTBI and LOC > 30 min for moderate-to-severe TBI. However, in experimental TBI models, there is no standard guideline for assessing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
(151 reference statements)
0
5
0
Order By: Relevance
“…The impact energy was obtained by multiplying the mass of the weight (kg) with the gravity force (9.8 m/s 2 ) and the height from where it is launched (0.91 or 0.60 m, respectively), as previously reported ( 31 ). The loss of the righting reflex (loss of consciousness) was evaluated based on the latency of self-righting immediately after the injuries, which correlates with injury severity ( 32 ). The average time elapsed before recovery of the righting reflex was significantly increased in both rmTBI ( P < 0.0001) and rlmTBI ( P < 0.0001) mice, compared with the sham controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The impact energy was obtained by multiplying the mass of the weight (kg) with the gravity force (9.8 m/s 2 ) and the height from where it is launched (0.91 or 0.60 m, respectively), as previously reported ( 31 ). The loss of the righting reflex (loss of consciousness) was evaluated based on the latency of self-righting immediately after the injuries, which correlates with injury severity ( 32 ). The average time elapsed before recovery of the righting reflex was significantly increased in both rmTBI ( P < 0.0001) and rlmTBI ( P < 0.0001) mice, compared with the sham controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The time duration for loss of righting reflex (LRR) after injury/sham and discontinuation of anesthesia is comparable to the duration of lost consciousness in TBI patients. 31 LRR was used as an index of injury severity in this study as used before. 32–35 On the first day of injury, LRR was considerably longer (366 ± 53 sec) in rmFPI mice than in shams (138 ± 110; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Aside from having no connection to DoC, its use as an outcome measure is controversial, and though some studies have included it in their results, high variability observed with LRR has been widely reported. As noted in a recent review comparing the prognostic value of brief loss of consciousness that may occur in human mild TBI versus LRR in rodent studies: “LRR is a highly heterogeneous measure subject to large individual variability, such that two rodents experiencing the same injury with identical parameters may have drastically different LRR.” 8 Independent of the mischaracterization of brief LRR as a model of DoC, the extremely low variability in LRR reported in this paper is another anomaly that calls into question its integrity and reliability (Box 1 ).…”
mentioning
confidence: 80%